Body segment inertial parameters of elite swimmers using DXA and indirect methods - Rossi, M.; Lyttle, A.; El-Sallam, A.; Benjanuvatra, N.; Blanksby, B. (Journal of Sports Science & Medicine, 2013)
As accurate body segment inertial parameters (BSIPs) are difficult to obtain in motion analysis, this study computed individual BSIPs from DXA scan images. Therefore, by co-registering areal density data with DXA grayscale image, the relationship between pixel color gradient and the mass within the pixel area could be established. Thus, one can calculate BSIPs, including segment mass, center of mass (COM) and moment of inertia about the sagittal axis (Ixx). This technique calculated whole body mass very accurately (%RMSE of < 1.5%) relatively to results of the generic DXA scanner software. The BSIPs of elite male and female swimmers, and young adult Caucasian males (n = 28), were computed using this DXA method and 5 other common indirect estimation methods. A 3D surface scan of each subject enabled mapping of key anthropometric variables required for the 5 indirect estimation methods. Mass, COM and Ixx were calculated for seven body segments (head, trunk, head + trunk, upper arm, forearm, thigh and shank). Between-group comparisons of BSIPs revealed that elite female swimmers had the lowest segment masses of the three groups (p < 0.05). Elite male swimmers recorded the greatest inertial parameters of the trunk and upper arms (p < 0.05). Using the DXA method as the criterion, the five indirect methods produced errors greater than 10% for at least one BSIP in all three populations. Therefore, caution is required when computing BSIPs for elite swimmers via these indirect methods, DXA accurately estimated BSIPs in the frontal plane.